Pengembangan Media Audio Visual Dalam Meningkatkan Kemampuan Kognitif Anak Kelompok B TK Damhil - Natalia; Ardini, Pupung Puspa; Arifin, Irvin Novita (Student Journal of Early Childhood Education, 2024)
This research was carried out with the aim of knowing the development of audio-visual media in improving the cognitive abilities of group B children at the Damhil Darma Wanita Persatuan Kindergarten, Gorontalo State University, Gorontalo. The method used in this research is the research and development method. There are six stages, namely potential and problem analysis, data collection, product design, design validation, design revision, and product testing. From the data analysis that has been carried out, it can be concluded that the development of audio-visual media in improving the cognitive abilities of group B children has been declared valid.